Surveys on recent developments in algebraic geometry - Summer Research Institute on Algebraic Geometry (Salt Lake City, Utah 6-10 Jul, 2015); Coskun, Izzet; De Fernex, Tommaso; Gibney, Angela (Providence : American Mathematical Society, 2017)
These papers give succinct and thorough introductions to some of the most important and exciting developments in algebraic geometry in the last decade. Included are descriptions of the striking advances in the Minimal Model Program, moduli spaces, derived categories, Bridgeland stability, motivic homotopy theory, methods in characteristic $p$ and Hodge theory.
B. Lehmann, A snapshot of the Minimal Model ProgramZ. Patakfalvi, K. Schwede, and K. Tucker, Positive characteristic algebraic geometryO. Tommasi, The geometry of the moduli space of curves and abelian varietiesJ. Huizenga, Birational geometry of moduli spaces of sheaves and Bridgeland stabilityE. Clader, Gromov-Witten theory: From curve counts to string theoryD. Chen, Teichmuller dynamics in the eyes of an algebraic geometerA. Auel and M. Bernardara, Cycles, derived categories, and rationalityC. Robles, Degenerations of Hodge structureD. Erman and S. V. Sam, Questions about Boij-Soderberg theoryB. Antieau and E. Elmanto, A primer for unstable motivic homotopy theory.
Includes bibliographical references.
Keywords: Algebraic geometry -- Congresses